OVERPOPULATION AS INSPIRATION IN CREATING ILLUSTRATION ART - Ayu Rahma Fajarria (Universitas Negeri Semarang, 2025)
Overpopulation is a problem that arises from an uncontrolled number of people. This issue is often underestimated, which led the authors to choose overpopulation as the subject matter of this study project. This study discusses illustration artworks created by combining various manual techniques. The use of diverse manual techniques aims to produce artistic and appealing impressions to convey the impacts of overpopulation. These illustrations are intended to raise awareness of the urgency of overpopulation and to encourage audiences to take wise action in responding to it. The visual representation of overpopulation impacts was created using hatching, blocking, poster paint, and watercolor techniques. Selective color was used to create monochrome elements in certain objects to add a dramatic effect and emphasize mood differences in the artworks. This study resulted in 11 illustration pieces in various sizes and media, namely: 4 works on A1 paper, 4 works on yellow board measuring 65 cm × 78 cm, and 3 works on fabric sheets measuring 115 cm × 150 cm. The impacts of overpopulation highlighted in this study include traffic congestion, increasing crime rates, the potential submergence of Jakarta, environmental pollution, declining human resource quality, pressure on natural resources, rising unemployment, slum settlements, food crises, social inequality, and the relationship between human population and the environment. The visual forms of the illustrations are imitations of real situations that have been altered and rearranged into unnatural compositions. In addition to producing illustration works, this project is also expected to inspire and encourage younger generations to be more critical in facing the issue of overpopulation.